2021
DOI: 10.1088/1742-6596/1722/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison multi-layer perceptron and linear regression for time series prediction of novel coronavirus covid-19 data in West Java

Abstract: Until now, the pandemic conditions of Covid-19 are still ravaging the world, even in Indonesia and West Java. Various attempts have been made to stop it. West Java implements Large Scale Social Restrictions, is known as Pembatasan Sosial Skala Besar (PSBB). However, over time, a discourse emerged to loosen PSBB. One of the World Health Organization’s (WHO) requirements to loosen is the effective reproduction rate of Corona Virus cases below 1. Therefore, this study focuses on predicting the number of cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…According to the present data trend, West Java had zero instances on several occasions in May but reported an increase in July 2020 [8]. If the government intends to loosen limits, it must consider the possibility of future instances.…”
Section: Introductionmentioning
confidence: 72%
“…According to the present data trend, West Java had zero instances on several occasions in May but reported an increase in July 2020 [8]. If the government intends to loosen limits, it must consider the possibility of future instances.…”
Section: Introductionmentioning
confidence: 72%
“…Research that specifically addresses the prediction of new cases of COVID-19 can be found in a number of machine-learning studies. Yulita et al studied it for a province in Indonesia with traditional machine learning [11]. The use of deep learning has also been applied to this prediction [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hopefully, this chatbot can help residents obtain comprehensive, complete, and targeted vaccine information. So that residents have sufficient knowledge about vaccines and are confident to vaccinate (Yang et al, 2021;Yulita et al, 2021;Nuanmeesri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%